2020
DOI: 10.1177/0363546520968289
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Effect of Platelet-Rich Plasma in Reducing Donor-Site Pain After Anterior Cruciate Ligament Reconstruction

Abstract: Background: Anterior cruciate ligament reconstruction (ACLR) has a high incidence among sports players, and one important side effect of the surgery is graft donor site morbidity. Although some evidence suggests that application of platelet-rich plasma (PRP) during ACLR reduces pain and improves knee function, it is not a universal finding. Purpose: To perform a meta-analysis of previous studies testing the effects of PRP on donor site morbidity after ACLR. Study Design: Systematic review and meta-analysis. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Platelet alpha granules produce growth factors, which cause chemotaxis, cell migration, angiogenesis, proliferation, differentiation, and matrix synthesis. PRP is gradually making its way to the forefront of sports and rehabilitation medicine, and its involvement in many soft injuries has recently become the focus of study (Huang et al, 2020;Andrade et al, 2021;Hohmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet alpha granules produce growth factors, which cause chemotaxis, cell migration, angiogenesis, proliferation, differentiation, and matrix synthesis. PRP is gradually making its way to the forefront of sports and rehabilitation medicine, and its involvement in many soft injuries has recently become the focus of study (Huang et al, 2020;Andrade et al, 2021;Hohmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with that of another study [ 11 ]. While some researchers [ 12 ] have concluded that PRP had no effect on either post-operative knee pain or functional improvement, others found that, while PRP did not appear to improve post-operative knee function, it could relieve post-operative pain [ 13 , 14 ]. Our results did not indicate that pain relief was greater in the study group compared with that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…65 Studies have shown that the use of PRP during tendon implantation into bone tunnel can induce fibrocartilage formation to promote fibrocartilaginous enthesis healing and relieve pain. 61,66 However, because of individual differences, the concentration and platelet activity of autologous PRP are difficult to control. 67 Furthermore, the American Academy of Orthopaedic Surgeons (AAAS) clinical practice guidelines state that there is no high level of evidence to support the use of platelet-derived products for biologically enhanced RCR, and that the evidence for the reduction of RCR with PRP is limited.…”
Section: Limitations Of Existing Therapiesmentioning
confidence: 99%